Analisis Pendidikan Agama Islam Dan Pendidikan Akhlak Perspektif Al-Ghazali - Asy'arie, Bima Fandi; Arif Ma’ruf, Rachmad; Ulum, Anharul (LP2M Universitas Islam Ahmad Dahlan, 2023)
This study aims to discover Al-Ghazali views on Islamic religious and moral education. This research uses literature research with a qualitative approach. The author wants to collect literature data on Al-Ghazali analysis related to Islamic religious education and moral education. Iman Ghazali said that Islamic education aims to shape the individual in the world and the Hereafter fully. According to Al-Ghazali, the main purpose of Islamic education is to have taqarrub to Allah the Khaliq. He says the person who always draws close to God is perfect. According to Al-Ghazali, morality is defined as Al-Khuluq, a continuous trait or state of behavior that encourages action naturally and easily without thought or consideration. Moral education in the division of Al-Ghazali, there are three dimensions, namely the self-dimension, the social dimension, and the metaphysical dimension.